1986
DOI: 10.1002/jmor.1051900309
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies of the spinal cord in tetraodontiformes fishes

Abstract: The spinal cord of two tetraodontiform fishes, the Japanese file fish (Navodon modestus) and the panther puffer (Takifugu pardalis), are unusual among vertebrates in having a markedly abbreviated spinal cord with a long and flattened filum terminale. Only the rostral short part of the cord of both species is cylindrical; the greater part of the cord is markedly flat. The majority of the spinal nerve roots leave the short cylindrical part. The flattened part of the cord contains the central canal, myelinated ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…They have a conspicuously short spinal cord proper and an abnormally long filum terminale. Thus, we suggested that the peculiarity of the sunfish spinal cord may be not attributable to its body plan but may be common to the tetraodontiform fishes (Uehara and Ueshima, 1986). In this study, our suggestion was corroborated, as the spinal cord of the tiger puffer is similar to that of the panther puffer (Takifugu paradalis).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…They have a conspicuously short spinal cord proper and an abnormally long filum terminale. Thus, we suggested that the peculiarity of the sunfish spinal cord may be not attributable to its body plan but may be common to the tetraodontiform fishes (Uehara and Ueshima, 1986). In this study, our suggestion was corroborated, as the spinal cord of the tiger puffer is similar to that of the panther puffer (Takifugu paradalis).…”
Section: Discussionsupporting
confidence: 82%
“…Recently, we showed that the spinal cord proper in the order Tetraodontiformes, including the sunfish, is markedly reduced in length, and that the greater part of the vertebral canal is filled with the cauda equina, in the center of which the filum terminale can be traced. Thus, the shortness of the spinal cord proper does not directly relate to body proportions, since most species of the order Tetraodontiformes have ordinary body proportions (Uehara and Ueshima, 1986).…”
mentioning
confidence: 99%
“…In G‐II‐2, the spinal cord tapers abruptly at its caudal end forming the flat filum terminale. Although the flat filum terminale is not similar in appearance to the filum terminale in mammals, anurans, the Molidae and the Ostraciidae, we confirm the flat filum terminale as the true filum terminale based on its morphological characteristics, as described by Uehara and Ueshima ().…”
Section: Discussionsupporting
confidence: 72%
“…Owen (1866) also noted that the spinal cord in the Diodontidae and Tetraodontidae is short. Uehara and Ueshima (1986), and Uehara et al (2000) reported macroscopically, histologically, and embryologically that the spinal cord in the Tetraodontidae and Monacanthidae is prominently shortened, forming a flat filum terminale with the cauda equina. They suggested that the spinal cord might be shortened in tetraodontiform fishes in general.…”
Section: Introductionmentioning
confidence: 99%
“…In at least some vertebrates, the Filum Terminale appears to be more of a caudal extension of the spinal cord than a connective tissue tether (Rethelyi et al, 2004). Among vertebrates in which the spinal cord terminates without a conus medullaris, the portion of the vertebral canal length occupied by the spinal cord is highly variable (up to none at all, for example, Uehara & Ueshima, 1986).…”
Section: Introductionmentioning
confidence: 99%